UJI DAYA HAMBAT EKSTRAK BATANG TUMBUHAN Harrisonia perforata Merr. TERHADAP PERTUMBUHAN BAKTERI Shigella dysentriae - Dewi Permatasari; Ramadhanil Ramadhanil; Syariful Anam; Ivan Ivan (Biology Department, Mathematics and natural science, Tadulako University, 2015)
The research entitled inhibition test of stem extract of Harrisonia perforata Merr. on the growth of bacteria Shigella dysentriae has been conducted from April - May 2014. The objective of the research was to study the inhibition stem extract of H. perforate Merr. on the bactery studied. The extraction was used reflux method. The experiment was arranged in Completely Randomized Designed (CRD) by 4 treatments (concentrate extract 60%, 80%, 100% and Contrimoxazale 1% as positive control) and 3 repetitions. The result showed that the best of extract concentrate to inhibite of bacterial growth was 100%. The treatment by 60% and 80% were not significant different statistically. Keywords : Harrisonia perforata Merr., Shigella dysenriae, Extract concentrate, Inhibition zone.